Transcranial Magnetic Stimulation: Basic Principles and Clinical Applications in Migraine. Issue 3 (28th December 2016) - Barker, Anthony T.; Shields, Kevin
Abstract : Purpose: Transcranial magnetic stimulation (TMS) is a neurophysiological technique with a long established pedigree of safety, tolerability, and efficacy. Initially TMS was used to study the function of the cerebral cortex, but it has now become a treatment for migraine, one of the most common and debilitating neurological conditions. In this review we discuss the scientific background and development of the technique. We explore its application for the treatment of migraine and ponder the possible mechanisms of action in this most common neurological condition. Overview : The generation of brief magnetic pulses by a suitable coil can induce electrical fields in the body. When applied to the cerebral cortex, currents are painlessly induced in cortical neurons. These currents can lead to neuronal depolarization and may influence cortical excitability by means that are as yet not fully understood. This ability to modulate cortical excitability has been exploited as a treatment for migraine with aura. Aura is implicated in the pathophysiology of migraine. Experimental studies have shown that transcranial magnetic pulses can block waves of cortical spreading depression – the experimental equivalent of migrainous aura. Discussion: Migraine is a debilitating condition characterized by headache, nausea, and sensory hypersensitivity. It may affect up to 15% of the population, yet current drug treatments are often poorly tolerated. Clinical studies have shown that TMS is an effective treatment for migraine. In addition, it has the added advantages of being safe and well tolerated by patients.